Design and analysis of energy harvester using MEMS based Cantilever with variable perforations - Prasad, G.R.K; Siddaiah, N.; Sanjeev, P.; Raviteja, A.; Karunya, P.; Priyanka, P.S. (International Journal of Engineering and Technology, 2017)
This paper represents the design and analysis of energy harvester using MEMS based cantilever with PMN-PT single crystal properties which has excellent piezoelectric properties while compared to other piezoelectric materials like PZT thick film. The design is analysed using COMSOL multi physics which is used for many MEMS operations and also problems related to physics with many mathematical calculations with better efficiency and ease to design. We designed a cantilever with PMN-PT properties which has good coupling coefficient and increased perforations in number in form of square and circular. We tested the displacement sensitivity i.e., the variation of displacement at different eigen frequencies with increase in number of perforations. We observe output voltage by designing electromechanical analysis and variation in output capacitance ofÂ  2 .41 x 10-22 Farads is observed.